Analisis Kesalahan Berbahasa dalam Imla’ Mahasiswa IAIN ‎Salatiga - Syamsiyah, Barid (IAIN Salatiga, 2019)
This study aims to describe and analyze errors in the use of imla principles through a case study on students who learn Arabic at IAIN Salatiga, especially the imla’ subject. This study used a qualitative approach by including numbers as the reinforcement in drawing conclusions. The method used to collect data in this study included documentation, observation, and interviews. Whereas in analyzing the data, researchers used the Rusydi Ahmad Tha'imah’s method which included three steps of analysis, namely identification of errors (ta'rīf al-khatha'), description and classification of errors (tausīf al-khata') and interpretation and explanation of errors (tafsīr al-khatha'). The results of this study indicate that among the causes of errors, being one of them is due to linguistic factors namely writing rules and non-linguistic factors, as the students come from different schools or the level of ability of the students, in which students come from madrasa schools and public schools.